Potential habitat suitability of Iraqi amphibians under climate change - Emad Kaky (Society for Indonesian Biodiversity, 2020)
Abstract. Kaky E. 2020. Potential habitat suitability of Iraqi amphibians under climate change. Biodiversitas 21: 731-742. Biodiversity management and conservation planning are two techniques for reducing the rate of biodiversity loss, especially under the effect of climate change. Here 289 records of five species of amphibians from Iraq and seven environmental variables were used with MaxEnt to predict potential habitat suitability for each species under current and future conditions, using the 5th IPCC assessment  (RCP 2.6 and RCP 8.5 for the year 2050). The models suggest that annual precipitation and the mean temperature of the wettest quarter are the main factors that shape the distributions of these species. The estimated current habitat suitability was closely similar to that for 2050 under both scenarios, with a high niche overlap between them for all species. Among species, there were low niche overlaps between the frogs Bufo viridis, Hyla savignyi and Rana ridibunda, and also between the salamanders Neurergus crocatus and Neurergus microspilotus. Future sampling should focus on areas not currently covered by records to reduce bias. The results are a vital first step in long-term conservation planning for these species. Via sharing these results with decision-makers and stakeholders a crucial conservation actions need to increase Iraqi Protected Areas to avoid losing biodiversity in Iraq especially the unique populations and threaten species.